Effects of contamination and warming on ragworms Hediste diversicolor : a laboratory experiment with Oder estuary sediments - Duy Nghia Pham and Anja Ruhl and Kathrin Fisch and Safia El Toum and Susanne Heise and Inna M. Sokolova (Estuarine, coastal and shelf science, 2024)
Knowledge about the effects of sediment contamination on estuarine benthos has come mainly from observational studies and spiking experiments. There is a lack of experimental studies with field-contaminated sediments, especially those assessing the combined effects of contamination and other environmental stressors. Here we investigated the biomarker responses of ragworms Hediste diversicolor to contaminated sediments and warming. Ragworms were exposed to sediments with different contamination levels from the Oder estuary (German-Polish border) at 10 and 20 °C for three weeks. The most contaminated sediments induced dicarbonyl stress, but did not result in enhanced detoxification, significant oxidative stress, or impaired energy balance. Warming altered antioxidant defense in ragworms and increased their energy reserves. The effects of contamination and warming were generally mild, and the interactive effects were absent. This study suggests the relatively high resilience of H. diversicolor to multiple stressors.
Keywords: Odra and Elbe Estuary; biomarker in response to temperature and contminants; sediment